2012
DOI: 10.4196/kjpp.2012.16.6.423
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen/Glucose Deprivation and Reperfusion Cause Modifications of Postsynaptic Morphology and Activity in the CA3 Area of Organotypic Hippocampal Slice Cultures

Abstract: Brain ischemia leads to overstimulation of N-methyl-D-aspartate (NMDA) receptors, referred as excitotoxicity, which mediates neuronal cell death. However, less attention has been paid to changes in synaptic activity and morphology that could have an important impact on cell function and survival following ischemic insult. In this study, we investigated the effects of reperfusion after oxygen/glucose deprivation (OGD) not only upon neuronal cell death, but also on ultrastructural and biochemical characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 64 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…NMDA glutamate receptors participate in learning and memory. Overstimulation of these receptors by excess of glutamate can cause cell death during glucose and oxygen deprivation (Jung et al, 2012 ) and memory deficits due to xenobiotic exposure (Olney et al, 2000 ; Li et al, 2012 ). L-cys 2/ L-glu, L-cys and L-glu transporters participate in GSH synthesis in the CNS and are modulated by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA glutamate receptors participate in learning and memory. Overstimulation of these receptors by excess of glutamate can cause cell death during glucose and oxygen deprivation (Jung et al, 2012 ) and memory deficits due to xenobiotic exposure (Olney et al, 2000 ; Li et al, 2012 ). L-cys 2/ L-glu, L-cys and L-glu transporters participate in GSH synthesis in the CNS and are modulated by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…This vulnerability has been associated with postischemic expression of GluR2 lacking Ca ++ permeable receptors at CA1 synapses (Colbourne et al, ) and to hyperexcitability of the CA3 afferents (Ye et al, ). Yet morphological and biochemical modifications have been demonstrated in the CA3 area after OGD (Dennis et al, ; Jung et al, ) while delayed neuronal death has been demonstrated on in vitro DG granular cells after long glucose deprivation (Newell et al, ) or after OGD preceded by high glucose preincubation (Rytter et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tissue slice technique is popular in brain research [ 22 ] while its application in the lung physiology and pathophysiology is not widely applied yet. In a previous study, Wholsen et al used human PCLS sensitized with serum from allergy patients (passive sensitization), during the incubation period in vitro .…”
Section: Discussionmentioning
confidence: 99%